Service quality, brand equity, and foreign collaboration: Building sustainable competitive advantage in Indonesian private universities - Rana, Junaid Ali Saeed; Nawaz, Ahmad (Jurnal Manajemen dan Pemasaran Jasa, 2025)
The increasing presence of foreign universities in Indonesia’s higher education landscape poses both opportunities and competitive pressures for local private institutions. This study investigates how service quality, customer-based brand equity, and foreign university collaboration interact to foster sustainable competitive advantage within this evolving transnational education environment. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) on survey data from 211 students, the findings confirm that service quality significantly enhances customer-based brand equity, which in turn strengthens both foreign collaboration and long-term competitiveness. The analysis further identifies foreign collaboration as a mediating mechanism. It validates a sequential pathway, whereby service quality improves brand equity, which subsequently enables international collaboration and ultimately enhances competitive advantage. By applying a glocalization lens, this research highlights the importance of balancing global standards with local regulatory alignment, student expectations, and cultural relevance. The study contributes to higher education service marketing by providing actionable insights for private universities seeking to improve institutional positioning and for foreign universities pursuing localized expansion.